Wear-resistant hard-surface surfacing flux-cored wire and preparation method thereof
By preparing wear-resistant hard surface surfacing flux core welding wire, and using multiple drawing and annealing treatments to form hard boron, the problem of early failure of hot forging molds is solved, the hardness and wear resistance of the mold are improved, and titanium permeates. The treatment enhances corrosion resistance and extends the service life of the mold.
Patent Information
- Application Number
- CN202411233737.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Existing hot forging molds are prone to early failure under harsh working conditions, resulting in short service life and require efficient repair methods to extend their service life.
A method of preparing a wear-resistant hard surface surfacing flux core welding wire is adopted, by ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, The materials such as molybdenum trioxide are mixed and ground into a core powder, filled into the steel strip, and then drawn and annealed for multiple times. Finally, pretreated in a titanium tetrachloride atmosphere to form a high-power welding wire with high hardness and wear resistance.
The welding wire forms hard borides in the clad metal, which improves hardness and wear resistance, and enhances corrosion resistance and rust resistance through titanium penetration, extending the service life of the mold.
Smart Images

Figure BDA0005027090690000061 
Figure BDA0005027090690000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flux-cored welding wires, in particular to a wear-resistant hardfacing flux-cored welding wire and a preparation method thereof. Background Art
[0002] Hot forging forming process is an advanced processing method with high production efficiency, good workpiece quality and saving raw materials. It is widely used in machinery, locomotives, automobiles, tractors, aviation, light industry, petrochemicals, and power industries. There is a great demand for hot forging dies in industrial production. Due to the poor working conditions and short service life of hot forging dies, early failures such as bag opening, wear, collapse, and hot and cold fatigue often occur. Therefore, it is of great economic significance to repair the hot forging dies by surfacing welding to extend their service life.
[0003] Flux-cored welding wire, also known as powder-cored welding wire or tubular wire, can be divided into two categories: gas-entrained and non-gas-entrained. The outer surface of the flux-cored welding wire is the same as that of the solid welding wire, which is made of low-carbon steel or low-alloy steel with good plasticity, while the inner side is added with a flux core to give the welding wire different welding functions. The manufacturing method of flux-cored welding wire is usually to first roll the steel strip into a U-shaped cross-section, then fill the flux core prepared according to the dosage into the U-shaped steel strip, roll it tightly with a rolling mill, and then draw it into flux-cored welding wires of different specifications. Summary of the invention
[0004] The object of the present invention is to provide a wear-resistant hardfacing surfacing flux-cored welding wire and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a wear-resistant hardfacing flux-cored welding wire, comprising the following preparation steps:
[0006] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide, and grinding to obtain a core powder;
[0007] (2) rolling the steel strip into a U-shaped groove;
[0008] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, drawn, and annealed at 630-650°C for 45-53 minutes to obtain the welding wire blank;
[0009] (4) placing the welding wire blank in the equipment and treating it at 930-950° C. for 10-20 min in a gas atmosphere to obtain a pretreated welding wire;
[0010] (5) The pretreated welding wire is drawn and annealed at 630-650°C for 45-53 minutes to obtain a wear-resistant hardfacing flux-cored welding wire.
[0011] Furthermore, in step (1), the mass ratio of the ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride and molybdenum trioxide is 5-8: 2.0-2.8: 3-5.5: 9.5-11.1: 12.6-13.9: 50: 1-3: 3-6: 1-2.
[0012] Furthermore, the grinding in step (1) is performed to a size of 150 to 200 meshes.
[0013] Furthermore, the thickness of the steel strip in step (2) is 0.25-0.40 mm, and the width is 7.5-12.5 mm.
[0014] Furthermore, the diameter of the U-shaped groove in step (2) is 3.0 to 3.4 mm.
[0015] Furthermore, the step (3) is drawing to a diameter of 2.0 to 2.8 mm.
[0016] Furthermore, the gas atmosphere in step (4) is titanium tetrachloride gas.
[0017] Furthermore, the titanium tetrachloride gas is obtained by heating liquid titanium tetrachloride and vaporizing it in a vaporization chamber, and the pressure of the vaporization chamber is 10 to 30 kPa.
[0018] Furthermore, the step (5) is performed by drawing to a diameter of 1.4 to 2.0 mm.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The flux-cored welding wire prepared by the present invention forms hard borides in the cladding metal crystal matrix, thereby giving the cladding metal a very high hardness, and boron carbide is also distributed in the cladding layer, thereby improving the wear resistance. The cladding metal formed by the flux-cored welding wire prepared by the present invention has good fluidity, and does not require a shielding gas during welding, thereby saving costs. The present invention wraps the powdered flux core in a steel shell to improve the corrosion resistance of the welding wire, and through the first drawing, each powder is combined with each other, and a pinning grain boundary is formed on the surface of the steel shell, which can refine the grains and improve the hard surface quality. Then, a titanium infiltration treatment is performed to embed titanium elements in the surface steel shell, improve the corrosion resistance of the surface, and improve the rust resistance of the welding wire. Then, a second drawing treatment is performed to allow the steel skin and titanium to be better melt-bonded, and further embedded in the steel shell, thereby improving the corrosion resistance and wear resistance of the welding wire. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 5:2.0:3:9.5:12.6:50:1:3:1, and grinding to 200 mesh to obtain a core powder;
[0024] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0025] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, and drawn to a diameter of 2.6 mm, and annealed at 640°C for 48 min to obtain the welding wire blank;
[0026] (4) placing the welding wire blank in the equipment and treating it at 930° C. for 10 min in a titanium tetrachloride gas atmosphere to obtain a pretreated welding wire;
[0027] (5) The pretreated welding wire is drawn to a diameter of 1.8 mm and annealed at 640° C. for 48 min to obtain a wear-resistant hardfacing flux-cored welding wire.
[0028] Example 2
[0029] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 5.7:2.2:3.6:9.9:13.0:50:1.5:3.7:1.2, and grinding to 200 mesh to obtain a core powder;
[0030] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0031] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, and drawn to a diameter of 2.6 mm, and annealed at 640°C for 48 min to obtain the welding wire blank;
[0032] (4) placing the welding wire blank in the equipment and treating it at 930° C. for 20 min in a titanium tetrachloride gas atmosphere to obtain a pretreated welding wire;
[0033] (5) The pretreated welding wire is drawn to a diameter of 1.8 mm and annealed at 640° C. for 48 min to obtain a wear-resistant hardfacing flux-cored welding wire.
[0034] Example 3
[0035] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 6.5:2.4:4.3:10.3:13.2:50:2:4.5:1.5, and grinding to 200 mesh to obtain a core powder;
[0036] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0037] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, and drawn to a diameter of 2.6 mm, and annealed at 640°C for 48 min to obtain the welding wire blank;
[0038] (4) placing the welding wire blank in the equipment and treating it at 940° C. for 15 min in a titanium tetrachloride gas atmosphere to obtain a pretreated welding wire;
[0039] (5) The pretreated welding wire is drawn to a diameter of 1.8 mm and annealed at 640° C. for 48 min to obtain a wear-resistant hardfacing flux-cored welding wire.
[0040] Example 4
[0041] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 7.3:2.6:4.9:10.7:13.6:50:2.5:5.2:1.8, and grinding to 200 mesh to obtain a core powder;
[0042] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0043] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, and drawn to a diameter of 2.6 mm, and annealed at 640°C for 48 min to obtain the welding wire blank;
[0044] (4) placing the welding wire blank in the equipment and treating it at 940° C. for 15 min in a titanium tetrachloride gas atmosphere to obtain a pretreated welding wire;
[0045] (5) The pretreated welding wire is drawn to a diameter of 1.8 mm and annealed at 640° C. for 48 min to obtain a wear-resistant hardfacing flux-cored welding wire.
[0046] Example 5
[0047] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 8:2.8:5.5:11.1:13.9:50:3:6:2, and grinding to 200 mesh to obtain a core powder;
[0048] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0049] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, and drawn to a diameter of 2.6 mm, and annealed at 640°C for 48 min to obtain the welding wire blank;
[0050] (4) placing the welding wire blank in the equipment and treating it at 950° C. for 20 min in a titanium tetrachloride gas atmosphere to obtain a pretreated welding wire;
[0051] (5) The pretreated welding wire is drawn to a diameter of 1.8 mm and annealed at 640° C. for 48 min to obtain a wear-resistant hardfacing flux-cored welding wire.
[0052] Comparative Example 1
[0053] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 8:2.8:5.5:11.1:13.9:50:3:6:2, and grinding to 200 mesh to obtain a core powder;
[0054] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0055] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed to obtain the welding wire blank;
[0056] (4) placing the welding wire blank in the equipment and treating it at 950° C. for 20 min in a titanium tetrachloride gas atmosphere to obtain a pretreated welding wire;
[0057] (5) The pretreated welding wire is drawn to a diameter of 1.8 mm and annealed at 640° C. for 48 min to obtain a wear-resistant hardfacing flux-cored welding wire.
[0058] Comparative Example 2
[0059] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 8:2.8:5.5:11.1:13.9:50:3:6:2, and grinding to 200 mesh to obtain a core powder;
[0060] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0061] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, and drawn to a diameter of 2.6 mm, and annealed at 640°C for 48 min to obtain the welding wire blank;
[0062] (4) The pretreated welding wire is drawn to a diameter of 1.8 mm and annealed at 640° C. for 48 min to obtain a wear-resistant hardfacing flux-cored welding wire.
[0063] Comparative Example 3
[0064] (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide in a mass ratio of 8:2.8:5.5:11.1:13.9:50:3:6:2, and grinding to 200 mesh to obtain a core powder;
[0065] (2) rolling the steel strip into a U-shaped groove with a diameter of 3.2 mm; the thickness of the strip is 0.32 mm and the width is 10 mm;
[0066] (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, and drawn to a diameter of 1.8 mm, and annealed at 640°C for 48 min to obtain the welding wire blank;
[0067] (4) The welding wire blank is placed in the equipment and treated at 950°C for 20 minutes in a titanium tetrachloride gas atmosphere to obtain a wear-resistant hardfacing flux-cored welding wire.
[0068] Effect example
[0069] Arc welding tests were performed on the flux-cored welding wires prepared by the preparation method of the present invention in the above-mentioned Examples 1 to 5 and the flux-cored welding wires prepared in Comparative Examples 1 to 3, and various mechanical properties of the deposited metal of the welded parts were measured, wherein the hardness (HRC) was measured according to the national standard GB / T230.1-2004 "Metal Rockwell Hardness Test Part 1 Test Method", and the wear resistance was measured according to the national standard GB / 12444.1-1990 "Metal Wear Test Method M Type Wear Test", and the results are shown in the following Table 1.
[0070] Among them, the welding process conditions are as follows:
[0071] Welding steel plate: Q235B steel plate (350mm×150mm×20mm)
[0072] Welding method: flat welding
[0073] Arc voltage: 25~28V
[0074] Welding current: 180~200A
[0075] Welding speed: 25cm / min
[0076] Wire feeding speed: 150cm / min
[0077] Table 1
[0078]
[0079]
[0080] The flux-cored welding wire prepared by the present invention forms hard borides in the cladding metal crystal matrix, thereby giving the cladding metal a very high hardness, and boron carbide is also distributed in the cladding layer, thereby improving the wear resistance. The cladding metal formed by the flux-cored welding wire prepared by the present invention has good fluidity, and does not require a shielding gas during welding, thereby saving costs. The present invention wraps the powdered flux core in a steel shell to improve the corrosion resistance of the welding wire, and through the first drawing, each powder is combined with each other, and a pinning grain boundary is formed on the surface of the steel shell, which can refine the grains and improve the hard surface quality. Then, a titanium infiltration treatment is performed to embed titanium elements in the surface steel shell, improve the corrosion resistance of the surface, and improve the rust resistance of the welding wire. Then, a second drawing treatment is performed to allow the steel skin and titanium to be better melt-bonded, and further embedded in the steel shell, thereby improving the corrosion resistance and wear resistance of the welding wire.
[0081] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a wear-resistant hardfacing flux-cored welding wire, characterized in that: The method comprises the following preparation steps: (1) mixing ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride, and molybdenum trioxide, and grinding to obtain a core powder; (2) rolling the steel strip into a U-shaped groove; (3) The flux core powder is filled into the U-shaped groove, and then the U-shaped groove is rolled and closed, drawn, and annealed at 630-650°C for 45-53 minutes to obtain the welding wire blank; (4) placing the welding wire blank in the equipment and treating it at 930-950° C. for 10-20 min in a gas atmosphere to obtain a pretreated welding wire; (5) The pretreated welding wire is drawn and annealed at 630-650°C for 45-53 minutes to obtain a wear-resistant hardfacing flux-cored welding wire.
2. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 1, characterized in that: The mass ratio of the ferrosilicon powder, chromium carbide, ferromanganese powder, nickel metal powder, borax, calcium carbonate, reduced iron powder, lanthanum fluoride, cerium fluoride and molybdenum trioxide in step (1) is 5-8: 2.0-2.8: 3-5.5: 9.5-11.1: 12.6-13.9: 50: 1-3: 3-6: 1-2.
3. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 1, characterized in that: The step (1) is grinding to a size of 150 to 200 meshes.
4. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 1, characterized in that: The thickness of the steel strip in step (2) is 0.25-0.40 mm, and the width is 7.5-12.5 mm.
5. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 1, characterized in that: The diameter of the U-shaped groove in step (2) is 3.0 to 3.4 mm.
6. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 1, characterized in that: Step (3) is drawing to a diameter of 2.0 to 2.8 mm.
7. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 1, characterized in that: The gas atmosphere in step (4) is titanium tetrachloride gas.
8. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 7, characterized in that: The titanium tetrachloride gas is obtained by heating liquid titanium tetrachloride and vaporizing it in a vaporization chamber, and the pressure of the vaporization chamber is 10-30 kPa.
9. The method for preparing a wear-resistant hardfacing flux-cored welding wire according to claim 1, characterized in that: Step (5) is drawing to a diameter of 1.4 to 2.0 mm.
Citation Information
Patent Citations
Low-temperature steel flux-cored wire
CN104400250A
Titanium carbide enhanced type residue-free wear-resisting surfacing flux-cored wire and preparation method thereof
CN104646860A
Marine submerged-arc welding composite sintered flux and preparing method thereof
CN105234578A
Environment-friendly high-wear-resistance flux-cored wire and preparation method thereof
CN111940948A
Powder wire
RU2467854C1
Cited By
Preparation method of wear-resistant hard-surface surfacing flux-cored wire
CN121223342A
